Predictors of somatic symptom persistence in patients with chronic kidney disease (SOMA.CK): study protocol for a mixed-methods cohort study. Issue 11 (17th November 2022) - Shedden-Mora, Meike C; Jessen, Birte; Schmidt-Lauber, Christian; Löwe, Bernd; Rösch, Michael; Dannemeyer, Hendrik; Gloy, Joachim; Van den Bergh, Omer; Huber, Tobias B
Abstract : Introduction: Seven of 10 patients with non-dialysis chronic kidney disease (CKD) experience burdensome persistent somatic symptoms (PSS). Despite the high prevalence and relevance for quality of life, disease progression and mortality, the pathogenesis of PSS in CKD remains poorly understood. The SOMA.CK study aims to investigate biopsychosocial predictors and their interactions for PSS in non-dialysis CKD and to develop a multivariate prognostic prediction model for PSS in CKD. Methods and analysis: The study is a mixed-methods cohort study with assessments at baseline, 6 and 12 months. It aims to include 330 patients with CKD stages G2–4 (eGFR=15–89 mL/min/1.73 m 2 ). Primary outcome is the CKD-specific somatic symptom burden assessed with the CKD Symptom Burden Index. Secondary outcomes include quality of life, general somatic symptom burden and functioning. The interplay of biomedical (eg, biomarkers, epigenetics), treatment-related (eg, therapies and medication) and psychosocial variables (eg, negative affectivity, expectations) will be investigated to develop a prognostic prediction model for PSS. In an embedded mixed-methods approach, an experimental study in 100 patients using an affective picture paradigm will test the effect of negative affect induction on symptom perception. An embedded longitudinal qualitative study in 40–50 newly diagnosed patients will use thematic analysis to explore mechanisms of symptom development after receiving a CKD diagnosis. SOMA.CK is part of the interdisciplinary research unit 'Persistent SOMAtic Symptoms ACROSS Diseases'. Ethics and dissemination: The study was approved by the Ethics Committee of the Hamburg Medical Association (2020-10195-BO-ff). Findings will be disseminated through peer-reviewed publications, scientific conferences, the involvement of our patient advisory board and the lay public. Focusing on subjective symptom burden instead of objective disease markers will fundamentally broaden the understanding of PSS in CKD and pave the path for the development of mechanism-based tailored interventions. Trial registration number: ISRCTN16137374 .